SISTEM INFORMASI PERSEDIAAN BAHAN KIMIA LABORATORIUM PENELITIAN DAN PENGUJIAN TERPADU UNIVERSITAS GADJAH MADA - , WIDO WILFAN GEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Inventory data processing chemicals in the Integrated Research and Testing Laboratory, Gadjah Mada University (LPPT UGM) has adopted a Stock Listing Information Systems Materials. However, existing systems are still not able to process the data inventory of chemicals as a whole, because the existing system is only limited stock of the data record available chemicals. While the purchase transaction data management, sale and use of chemicals, is still done by recording the transaction on the books. Data processing and transactions are still not computerized chemical inventory LPPT UGM can lead to a less efficient data processing, data management and file neatly piled up, and the bill of sale can cause loss of data and information is invalid and inaccurate so service given to less than optimal. Based on the issues outlined above, he built a Chemical Inventory Information System that can process data purchases, sales and consumption as well as better reporting. The system is built using CodeIgniter framework, HTML, PHP, CSS, Javascript, jQuery and MySQL data base. Chemical Inventory Information System can be used to process data purchase, sale and use of chemicals that can generate purchasing reports, sales reports and usage reports and stock reports chemicals that are more effective, accurate and necessary information becomes easier to obtain.